Images and Performative Vision in the Middle Ages - Bino, Carla Maria (Eikón / Imago, 2017)
During the Middle Ages, images had to be tied to the truth. Otherwise, they were considered idols. And the idols are always dangerous and, therefore, banned. So, to be justified, the imago had to be true or really refer to truth. It follows that the images were not considered just objects ‘to see’, but were perceived as almost ‘alive bodies’, real bodies: they could act as if were actually present. This essay studies the image concept in Christian thought, with particular attention to Eastern Europe, in connection to the patristic and conciliar sources. The result is the shift of its ontological meaning: contrary to the mimetic idea of greek-hellenistic culture, the christian image is an ‘impression of similarity’. This conceptual revolution implies change of visualization strategies, which are specifically performative: ‘seeing the icon’ is doing something which involves ‘physically’ the viewer, as if he came into a scene and became an actor.